2015
DOI: 10.1007/978-3-319-22723-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Glass+Skin: An Empirical Evaluation of the Added Value of Finger Identification to Basic Single-Touch Interaction on Touch Screens

Abstract: The usability of small devices such as smartphones or interactive watches is often hampered by the limited size of command vocabularies. This paper is an attempt at better understanding how finger identification may help users invoke commands on touch screens, even without recourse to multi-touch input. We describe how finger identification can increase the size of input vocabularies under the constraint of limited real estate, and we discuss some visual cues to communicate this novel modality to novice users.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Results from Antal et al [46] showed that these additional features enhance the accuracy of both processes. Hereby, these studies suggested a heuristic supporting the pattern analysis and recognition of tapping fingers by checking responding finger of each typing, similar to fingerprint identification [47,48]. Keystroke dynamics of finger force control for user authentication has become an active research area due to its low cost and ease of integration with existing security systems.…”
Section: Discussionmentioning
confidence: 99%
“…Results from Antal et al [46] showed that these additional features enhance the accuracy of both processes. Hereby, these studies suggested a heuristic supporting the pattern analysis and recognition of tapping fingers by checking responding finger of each typing, similar to fingerprint identification [47,48]. Keystroke dynamics of finger force control for user authentication has become an active research area due to its low cost and ease of integration with existing security systems.…”
Section: Discussionmentioning
confidence: 99%
“…Colley et al [3] and Goguey et al [7] compared their performance as well as users' preferences in Fitts' tasks. Roy et al also looked at their reaction times and error rates [28]. Finally, Wang et al evaluated the precision of different fingers in a tapping task [34].…”
Section: Comparing Fingersmentioning
confidence: 99%
“…Recent studies show that even for single-touch command selection, finger identification is a promising solution to increase the touch input vocabulary [14]. Robust finger identification sensing is on the horizon [15,16], but examples of the interaction it enables have only been isolated point designs without cohesive design.…”
Section: Introductionmentioning
confidence: 99%